MED19 and MED26 Are Synergistic Functional Targets of the RE1 Silencing Transcription Factor in Epigenetic Silencing of Neuronal Gene Expression - Ding, Ning (American Society for Biochemistry and Molecular Biology, 2009)
A key hub for the orchestration of epigenetic modifications necessary to restrict neuronal gene expression to the nervous system is the RE1 silencing transcription factor (REST; also known as neuron restrictive silencer factor, NRSF). REST suppresses the nonspecific and premature expression of neuronal genes in non-neuronal and neural progenitor cells, respectively, via recruitment of enzymatically diverse corepressors, including G9a histone methyltransferase (HMTase) that catalyzes di-methylation of histone 3-lysine 9 (H3K9me2). Recently, we identified the RNA polymerase II transcriptional Mediator to be an essential link between RE1-bound REST and G9a in epigenetic suppression of neuronal genes in non-neuronal cells. However, the means by which REST recruits Mediator to facilitate G9a-dependent extra-neuronal gene silencing remains to be elucidated. Here, we identify the MED19 and MED26 subunits in Mediator as direct physical and synergistic functional targets of REST. We show that although REST independently binds to both MED19 and MED26 in isolation, combined depletion of both subunits is required to disrupt the association of REST with Mediator. Furthermore, combined, but not individual, depletion of MED19/MED26 impairs REST-directed recruitment to RE1 elements of Mediator and G9a, leading to a reversal of G9a-dependent H3K9me2 and de-repression of REST-target gene expression. Together, these findings identify MED19/MED26 as a probable composite REST interface in Mediator and further clarify the mechanistic basis by which Mediator facilitates REST-imposed epigenetic restrictions on neuronal gene expression.